Konsep diri membaca dan minat baca pada siswa sekolah dasar - Roy Gustaf Tupen Ama; Rahma Widyana (Fakultas Psikologi, 2021)
Reading interest is very important for students in the learning process. This study aimed to determine the correlations between reading self-concept and students’ reading interest. In this study, the researcher used two scales namely scale of reading self-concept, and scale of students’ interest in reading. The population in this study were all students of grade 3,4,5 at “X” Sleman Elementary School in Yogyakarta, Indonesia. The sampling technique in this study was incidental sampling with a sample size of 124. The results of the analysis show that there is a correlation between reading self- concept and students’ reading interest with an r value of 0.855 (p < 0.01). It is important for elementary school students to form a reading self-concept so that a high reading self-concept will increase students’ reading interest.